ANALISIS NILAI MORAL DALAM NOVEL “LEMBARAN TERABAIKAN” KARYA NOIBE HALAWA - Gulo, Penunjuk Jalan; Ndruru, Mastawati; Waruwu, Lestari; Harefa, Noveri Amal Jaya (Jurnal Ilmu Budaya, 2024)
This research aims to find out and describe the moral values ​​contained in Noibe Halawa's Neglected Sheet. This research is a qualitative descriptive study. The data for this research are the texts in the novel Selamat Terabaikan by Noibe Halawa. The data analysis techniques are data collection, data reduction, data presentation, and drawing conclusions. Based on the results of the research and discussion of the novel Selamat Terabaikan by Noibe Halawa, several conclusions can be drawn, namely that the forms of moral values ​​contained in the novel Selamat Terabaikan include: the form of moral values ​​has three types, namely; the first is the form of moral values ​​in human relations with God which has variants in the form of believing and praying to God, and giving thanks; secondly, the manifestation of moral values ​​in humans' relationships with themselves has the variants of patience, sincerity, honesty, self-confidence, simplicity and surrender; Meanwhile, the form of moral values ​​in human relations with other humans is mutual help and caring for others. The most data found in the form of moral values ​​is the form of moral values ​​of human relationships with themselves. The total data that has been obtained as a manifestation of moral values ​​in this novel is 21 data.